Biomorphological and phytochemical parameters of Chelidonium majus L. in the conditions of Kungei-Alatau - Dostemessova, A.B.; Ametov, A.A.; Kurmanbayeva, M.S.; Izbastina, K.S. («Академик Е.А. Бөкетов атындағы Қарағанды университеті» КЕАҚ баспасы, 2023)
In the pharmaceutical industry, the stability o f the relationship between synthetic drugs and natural drugs has changed recently. This is because drugs made from natural plants are more in demand than chemically prepared drugs. The advantages o f herbal medicines are their low toxicity, a significant complex of biologically active compounds, the versatility o f pharmacotherapeutic effects, and the possibility o f long-term use without obvious adverse reactions. In addition to the therapeutic effect of the biologically active substances contained in the medicinal products, the preventive effect is also effective. Therefore, it is important to analyze the composition o f natural medicinal raw materials o f plant origin. The aim of the work is to study macrodiagnostic features and composition o f active natural compounds of medicinal plant Chelidonium majus L. C. majus plant collected in the Kungei Alatau region and medical, cosmetic and hygienic dry kits prepared on the basis of C. majus sold in pharmacies were used as the research object. Pharmacognosy, macroscopic and gas chromatography-mass spectrometry (GC-MS) methods were used in the research. The results o f the macroscopic analysis confirmed the conformity o f the composition and characteristics o f the finished raw materials in the samples. C. majus plant samples showed stable component composition of sufficient biologically active substances. All samples contained 3,7,11,15-Tetramethyl-2- hexadecen-1-ol, Phytol, Ethyl Oleate, 9,12-Octadecadienoic acid, ethyl ester, 9,12,15-Octadecatrienoic acid, ethyl ester, (Z, Z, Z), Methyl 19-methyl-eicosanoate, Protopine compounds were determined. Conducting clinical trials to evaluate the therapeutic potential o f the plant and its efficacy and safety in pharmaceutics is the basis for future research. The obtained results allow an objective assessment of the quality standards of pharmacopoeial medicinal plant C. majus materials.
Күнгей Алатау жағдайындағы Chelidonium majus L. өсімдігінің биоморфологиялық және фитохимиялық көрсеткіштері
Биоморфологические и фитохимические показатели Chelidonium majus L. в условиях Куигей-Алатау
Keywords: Chelidonium majus; pharmacology; medicine; medicinal plant; alkaloids; organic compounds; Kungei Alatau; preparation